Secondary Metabolites in the Arctic Sponge Haliclona viscosa - Spatial and Temporal Variation - Schmidt, Gesine (2010)
The metabolite screening of Haliclona viscosa yielded 21 3-alkyl pyridinium alkaloids whose structure was unknown before (haliclocyclin C, haliclamine K and J, dehydro-haliclamine J, dehydro-viscosaline E1, viscosamine D, dehydroviscosamine C and D) or had previously been suggested and could be refined or confirmed (haliclocyclin F1, haliclamine E and F, dehydro-haliclamine C, D, F, ambidehydro-haliclamine F and didehydro-haliclamine D, viscosaline B1, B2, E1 and E2, viscosamine B). The structure identification of haliclamines based on a mass spectrometric fragmentation study of the haliclamines; it forms part of this thesis and is enclosed in manuscript form to be published. New viscosalines and viscosamines were identified by evaluation of the high resolution mass spectra of a known viscosaline and viscosamine, and the observations concerning their fragmentation behavior are described in the presented thesis. Structure elucidation of 3-APAs that contain double bonds in the alkyl chains is in progress, as is the structure elucidation of still unknown 3-APAs in the crude extract eluting before 12 min and after 23 min. In the progress of developing a method that allows metabolite screening of different sponges by MALDI-MS, the Caribbean sponge Stylissa caribica was found to possess previously unknown compounds which were identified as the new cyclic heptapeptides stylissamides A-D. The stylissamides are very rich in proline and especially stylissamide B shows an interesting combination of amino acids, with three out of four prolines being arranged consecutively. Imposed by this configuration, the NMR signals of the stylissamides overlapped strongly but the structure elucidation could finally be achieved by a combination of extensive NMR and MS experiments. Das Metabolitenscreening in Haliclona viscosa ergab 21 3-Alkylpyridinalkaloide, deren Struktur vormals unbekannt war (Haliclocyclin C, Haliclamine K und J, dehydro-Haliclamin J, dehydro-Viscosalin E1, Viscosamin D, dehydro-Viscosamin C und D), oder deren ...